Probiotic intervention improves cholestatic parameters in patients with drug-induced liver injury: a real-world retrospective study - Li, Na; Liu, Penghui; Guo, Jiwu; Guo, Lingyun; Wang, Jizhen; Mou, Ziyuan; Mao, Jie (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to investigate the impact of gut microbiota intervention on the therapeutic outcomes in patients with drug-induced liver injury (DILI).MethodsA total of 120 patients with DILI who were hospitalized at the Second Hospital of Lanzhou University from January 2023 to December 2024 were retrospectively enrolled. Patients were divided into an intervention group and a control group based on whether they received gut microbiota intervention therapy. Quantitative data were presented as median and interquartile range, and the Mann–Whitney U test was used for intergroup comparisons. Categorical variables were compared between groups using chi-square tests. Logistic regression analysis was used to identify factors associated with liver injury severity and to evaluate the effect of gut microbiota intervention.ResultsAfter treatment, GGT, ALP, TBIL, DBIL and IBIL decreased significantly more in the intervention group than in the control group, and the differences were statistically significant (p < 0.01). Before treatment, the intervention group had a higher proportion of patients with grade 1 and grade 4 DILI, while the control group had more patients with grade 2 and grade 3 DILI. After treatment, the proportion of grade 1 patients in the intervention group increased significantly, whereas the proportion of grade 4 patients decreased markedly. These changes were statistically significant between the two groups (p < 0.01). Logistic regression analysis showed that the risk of liver injury was significantly reduced in the intervention group after treatment (OR = 0.018, p < 0.01). In terms of model prediction accuracy, the prediction rate for moderate liver injury was relatively high (91.0%), whereas the accuracy for acute liver failure and severe liver injury was lower. The overall prediction accuracy of the model was 75.0%. Pearson correlation analysis revealed that post-treatment DILI grade was significantly associated with treatment regimen, TBIL, ALP and GGT (p < 0.01).ConclusionProbiotic intervention significantly improved cholestasis-related parameters and reduced the severity of liver injury in patients with DILI. This real-world study provides novel clinical evidence supporting microbiota-targeted therapy as a promising adjunctive strategy, particularly for cholestasis-predominant DILI.